2013
DOI: 10.1097/rli.0b013e31828027c2
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Magnetic Resonance Imaging–Guided Cryoablation of Small Renal Tumors at 1.5 T

Abstract: Objectives-Real-time magnetic resonance imaging (MRI)-guided cryoablation has been investigated in open MRI systems with low magnetic fields (0.2-0.5 T). More advanced imaging techniques and faster imaging rates are possible at higher magnetic fields which often require a closed-bore magnet design. However, there is very little experience with real-time interventions in closed-bore 1.5 T MRI units. Herein, we report our initial experience with real-time MRI-guided cryoablation of small renal tumors using a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…If procedural radiation doses were to be curbed by the use of MRI or ultrasound for imaging guidance rather than CT, or if follow-up regimens were altered by the use of dual-energy CT or MRI, then perpatient costs may be substantially impacted [39,41,[48][49][50][51][52]. We elected not to conduct a formal cost-effectiveness analysis because downstream costs associated with radiationinduced cancers, which are expected to occur decades later, would have an associated level of uncertainty that is unreasonably high.…”
Section: Effects Of Radiation Exposure Associated With Renal Ablationmentioning
confidence: 97%
“…If procedural radiation doses were to be curbed by the use of MRI or ultrasound for imaging guidance rather than CT, or if follow-up regimens were altered by the use of dual-energy CT or MRI, then perpatient costs may be substantially impacted [39,41,[48][49][50][51][52]. We elected not to conduct a formal cost-effectiveness analysis because downstream costs associated with radiationinduced cancers, which are expected to occur decades later, would have an associated level of uncertainty that is unreasonably high.…”
Section: Effects Of Radiation Exposure Associated With Renal Ablationmentioning
confidence: 97%
“…The first MRI-guided clinical trials were reported in 1986 (13). Since then, MRI-guided clinical applications have been successfully applied to lesions in various anatomical regions, such as pancreatic, breast, prostate, lung tumor, and renal tumor lesions (14)(15)(16)(17)(18). After ∼20 years of clinical use, MRIguided breast biopsy has evolved into a routine method in Western European countries (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Although the results presented here focus primarily on brain tumors, the method may be extended to and used for the segmentation of other large solid tumors as well. Likewise, because the algorithm is extremely fast, one could potentially use this methodology for real-time tumor tracking during invasive procedures such as thermal ablation or cryoablation (31). …”
Section: Discussionmentioning
confidence: 99%